Planktonic foraminifera and calcareous nannofossils record in the upper Campanian-Maastrichtian pelagic deposits of the Malatya Basin in the Hekimhan area (NW Malatya, eastern Anatolia) - B. Sari; A. Yildiz; T. Korkmaz; M.R. Petrizzo (Cretaceous Research, 2016)
The uppermost Cretaceous (upper Campanian-Maastrichtian) pelagic successions from the Malatya Basin (NW Malatya, eastern Anatolia) were studied by 688 samples, which were collected from five stratigraphic sections in the Hekimhan area. The pelagic deposits conformably overlie rudist bearing shallow-water limestones and are overlain conformably by Maastrichtian dolomites and unconformably by Paleocene. -Eocene deposits, respectively.The pelagic successions in the Hekimhan area comprise the Kösehasan Formation at the base and the Zorbehan Formation at the top and reach up to 1100 m in thickness. The Kösehasan Formation rests over the neritic rudist-bearing limestones of the Güzelyurt Formation along a sharp contact and consists mainly of flysch-type sandstone-mudstone alternation with complete and partial Bouma sequences. The carbonate content of abundant planktonic foraminifera and nannoplankton-bearing 980-m-thick succession increases upwards and the formation passes gradually to the clayey limestones and marlstones of the Zorbehan Formation to the top. Occurrences of nannoplankton Lithraphidites quadratus Bramlette and Martini and Micula praemurus (Bukry) in the first beds of the Kösehasan Formation indicate that the age of the Kösehasan Formation and overlying Zorbehan Formation is of late Maasthrichtian. Another late Maastrichtian taxa Cribrosphaerella daniae Perch-Nielsen and Arkhangelskiella maastrichtiana Burnett are observed from the lowermost part of the succession. Maastrichtian planktonic foraminifera such as Contusotruncana walfischensis (Todd) and Globotruncanita pettersi (Gandolfi) were recorded through the successions. Although planktonic foraminifera are diverse and abundant particularly in the Kösehesan Formation, index late Maasthrichtian species were not encountered. Campanian and Santonian-Campanian planktonic foraminifera, e.g. Radotruncana calcarata (Cushman) and Globotruncanita elevata (Brotzen), obtained particularly from the lower part of the succession and calcareous nannofossils such as ...